STRIKE ON FISCAL REFORM IN COSTA RICA - Arguedas Abarca, María Fernanda (2022)
The central theme of this issue has been written by M. Sc. Sindy Mora Solano, Deputy Director of the Institute of Social Research of this university, which is inserted as an introduction to the central section. In the articles section there are various contributions on the topics of presidential campaigns, sociology of power, urban transformation, experiences in asylum situations, health system in indigenous populations, workplace harassment through images, models of representation of the collective LGBTI+ in audiovisual productions, knowledge about AIDS and discourses of sexuality in social networks.